LIS Education in Developing Countries : the Road Ahead. - Abdullahi, Ismael (IFLA publications., 2014)
The book contains relevant subjects and topics that address the future of LIS education in the developing world of Africa, Asia, and Latin America. Since last two decades the profile of LIS education, and their content are on the constant and persistent changes. LIS education is facing a fabulous task of managing and preparing future generation of library and information professionals.